Metagenomic and metabolomic analyses reveal differences in rumen microbiota between grass- and grain-fed Sanhe heifers - Zhang, Xinyu; Wang, Wei; Wang, Yajing; Cao, Zhijun; Yang, Hongjian; Li, Shengli (Frontiers in Microbiology, 2024)
Introduction: The aim of this study was to investigate the effects of diets on the composition and function of rumen microbiome and metabolites in Sanhe heifers. Methods: Metagenomic and metabolomic analyses were performed using rumen fluid samples collected from Sanhe heifers (n = 20) with similar body weights and ages from grass-fed and grain-fed systems. Results: The grain-fed group exhibited more intensive rumen fermentation than the grass-fed group. However, the grass-fed group exhibited carbohydrate metabolism and methane production higher than that of the grain-fed group; these increases were observed as a higher abundance of various bacterial phyla (Firmicutes, Bacteroidetes, Actinobacteria, Lentisphaerae, and Verrucomicrobia), families (Lachnospiraceae, Eubacteriaceae, and Eggerthellaceae), and the archaeal family Methanobacteriaceae. A comparison of genes encoding carbohydrate-active enzymes, using Kyoto Encyclopedia of Genes and Genome profiles, revealed noteworthy differences in the functions of rumen microbiota; these differences were largely dependent on the feeding system. Conclusions: These results could help manipulate and regulate feed efficiency in Sanhe cattle.